2020
DOI: 10.1177/1078087420908933
|View full text |Cite
|
Sign up to set email alerts
|

Are You Picking Up What I Am Laying Down? Ideology in Low-Information Elections

Abstract: In November 2017, New Orleans elected the first woman, and first Black woman, mayor in the city’s history. Voters were unable to rely on gender, race, or partisanship to differentiate between the candidates in the race. How, then, do voters make decisions absent traditional heuristics? Using an analysis of campaign materials and two-wave panel survey, we show that the candidates sent ideological signals with endorsements and issue foci and that voters responded by placing the candidates ideologically. Those vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 71 publications
1
18
0
Order By: Relevance
“…In the more specific context of municipal electoral politics, a large body of research has found that standard ideological and partisan positions are clearly relevant to municipal vote choice in Canada and the United States (Holman and Lay 2021;Lucas 2020a;Lucas and McGregor 2020;Sances 2018), but other factors, such as race (Hajnal and Trounstine 2014;Kaufmann 2004) and local policy issues (Oliver and Ha 2007) also affect municipal voting. Two excellent studies of mayoral voting in Vancouver, covering the 2002 and 2018 elections, have argued that ideology and policy issue attitudes were crucial predictors of mayoral vote choice (Cutler and Matthews 2005b;Rooij, Matthews, and Pickup 2020), though it is not yet clear if these findings apply to non-mayoral vote choice as well.…”
Section: The Structure Of Municipal Electionsmentioning
confidence: 99%
“…In the more specific context of municipal electoral politics, a large body of research has found that standard ideological and partisan positions are clearly relevant to municipal vote choice in Canada and the United States (Holman and Lay 2021;Lucas 2020a;Lucas and McGregor 2020;Sances 2018), but other factors, such as race (Hajnal and Trounstine 2014;Kaufmann 2004) and local policy issues (Oliver and Ha 2007) also affect municipal voting. Two excellent studies of mayoral voting in Vancouver, covering the 2002 and 2018 elections, have argued that ideology and policy issue attitudes were crucial predictors of mayoral vote choice (Cutler and Matthews 2005b;Rooij, Matthews, and Pickup 2020), though it is not yet clear if these findings apply to non-mayoral vote choice as well.…”
Section: The Structure Of Municipal Electionsmentioning
confidence: 99%
“…While most scholars continue to acknowledge that municipal jurisdictional limits and inter-municipal competition do constrain municipal attempts at redistributive policy making, a large body of evidence suggests not only that ideology plays an important role in municipal vote choice (Holman and Lay, 2021; Sances, 2018) but also that there is a clear relationship between municipal residents’ ideological positions and the policies that their municipalities enact (Tausanovitch and Warshaw, 2014; Einstein and Kogan, 2016). Moreover, this evidence consistently shows that ideological voting and policy responsiveness are equally apparent across municipalities of all population sizes (Sances, 2018; Schaffner et al, 2020).…”
Section: Local Ideology and Political Representationmentioning
confidence: 99%
“…A variety of evidence from observational data, surveys, and survey experiments suggests that in nonpartisan electoral settings, voters use information or signals about candidates’ partisanship when they are available (Schaffner, Streb and Wright 2001; Sen 2017; Squire and Smith 1988). Recent studies of local elections suggest that voters do indeed learn about candidates’ relative ideological positions over the course of a campaign—even when some common information shortcuts are absent or uninformative—and that evaluations of ideology influence voting behavior (Holman and Lay 2020; Sances 2018). For example, Holman and Lay (2020) focus on the 2017 mayoral elections in New Orleans, a race between two Black women, both Democrats.…”
Section: Why Are There So Many Business Executive Mayors?mentioning
confidence: 99%
“…Recent studies of local elections suggest that voters do indeed learn about candidates’ relative ideological positions over the course of a campaign—even when some common information shortcuts are absent or uninformative—and that evaluations of ideology influence voting behavior (Holman and Lay 2020; Sances 2018). For example, Holman and Lay (2020) focus on the 2017 mayoral elections in New Orleans, a race between two Black women, both Democrats. While voters could not differentiate the candidates based on partisanship, gender, or race, the authors find that the candidates signaled their ideology via endorsements and the issues they emphasized, which allowed voters to judge which candidate was more or less liberal.…”
Section: Why Are There So Many Business Executive Mayors?mentioning
confidence: 99%